Pro-inflammatory cytokines and pain - Kraychete, Durval Campos; Calasans, Maria Thais De Andrade; Valente, Camila Motta Leal (Springer Nature, 2006)
This review aims to describe the interaction between cytokines, glial cells and pain mechanism. Humans can identify an aggressive stimulus and memorize it for their own defense to face new threats through a withdrawal motor phenomenon and sympathetic nervous system activation. As the glial cells have the same receptors and transduction systems as neurons, there is dynamic interaction between these cells in the amplification of neuronal response to the peripheral or central aggression. In both, tissue injury activates endothelial cells, the microglia, the astrocytes, permeating the site with immune cells and producing cytokines and chemiokines. If the aggressive stimulus persists, glial responses' self-regulatory properties would not be able to maintain appropriate biochemical homeostasis making the neuron develop to cell dysfunction and programmed death. From the other side, in diseases with chronic or acute inflammatory process it is possible that cytokines induce responses in order to accelerate defensive enzymatic reactions, reduce pathogenic replication, increase immune cells proliferation, fix injured site and conserve energy. And so, cytokines can be recognized by neurons and used to provoke several intracellular reactions that will determine electric nervous activity alterations for undetermined time.
Citocinas pró-inflamatórias e dor
Keywords: Cytokines; Neuroplasticity; Pain